Pengaruh Intensitas Penggunaan Media Sosial dan Intensitas Komunikasi Orang Tua Anak Terkait Kegiatan Sekolah Terhadap Prestasi Belajar Siswa Pedesaan - Hesti Rahmawati, Widiastri; Naryoso, Agus (Interaksi Online, 2019)
This research was aimed to study the effect of intensity using social media and communication intensity of parents of children regarding school activities towards rural student learning achievements. The theory used is the Theory of Computer Mediated Communication (CMC) and Theory of Change. The sampling technique uses nonprobability sampling conducted by accidental sampling with a total sample of 50 people with the criteria of vocational high school students reaching 14-18 years in the Boyolali Rural Area and social media actively. Testing used a Simple Linear Regression Test. The results showed that there was participation using social media on student learning achievement with a significance of 0.004 less than 0.05. The intensity variables of social media use as much as 22.7% and 77.3% are needed by other factors such as interest in chat messenger aplication. In the parent communication variable, children related to school activities showed a significance of 0.002 with an influence on student learning achievement 17.9% and 82.1% by other factors such as parents' educational background.